ملامح نظرية السياق عند " ابن جني " " الخصائص " أنموذجاً - بصل محمد; بلة فاطمة (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
لقد تبوأت دراسة السياق مجالاً واسعاً في الدراسات اللغوية لأهميته الكبرى وقدرته الهائلة في توجيه المعنى ، فالدلالة المعجمية الحقيقية يقع الفهم عليها للوهلة الأولى ، أما الدلالة السياقية فهي تحتاج إلى قرينة لغوية أو لفظية للوصول إلى دلالتها المبتغاة . وقد أدرك علماء اللغة أن الكلام تحكمهُ مجموعة من القرائن والعلاقات ، بعضها داخلي يتعلق بالنظم ، وبعضها خارجي يتعلق بالموقف الذي تدور حوله الألفاظ . وسيتناول البحث ملامح نظرية السياق عند "ابن جني" في كتابه "الخصائص" ، حيث اعتمد على السياق في تناول النص اللغوي ، على مختلف المستويات المعجمية والدلالية والصرفية والصوتية . إنّ ما قام به "ابن جني" - وغيره من علماء اللغة - ليدل على القدر الكبير من الدقة والعمق في استيعاب الدرس اللغوي العربي لنظرية السياق . The study of "Context" has taken a wide space in the linguistic studies due to its great importance and tremendous ability in diirecting the meaning . The real dictionary indication gives the first instance understanding , while the context indication needs a linguistic presumption for reaching the targeted indication . The Linguists realized that speaking is controlled by a set of presumptions and relations , some of which are internal and related to the systems , while others are external and related to the situation about which the pronunciation is concerned . The research will handle the aspects of "Context" Theory for Ibn jinny in his book "The properties" , where he depended on the context in handling the linguistic text , at the various levels (dictionary , semantics , inflection , phonetics) . What Ibn jinny and other Linguists did reveals how much accuracy and depth is needed to comprehend the "Context" Theory linguistically .